102 minutes that changed America [videorecording (DVD)] (A&E Television Networks, 2008)
A stunning chronological record of the events of September 11, 2001, presenting a real time, moment-by-moment account of the World Trade Center collapse as seen by New Yorkers. Includes bonus documentary I-Witness to 9/11.